Estrategias de afrontamiento en adolescentes escolarizados con sintomatología depresiva (2022)
Given the difficulty adolescents have in dealing with their daily problems, which can lead to depression and/or suicide attempts, the aim of this study was to describe the coping strategies used by adolescents who present depressive symptoms. For this purpose, a descriptive quantitative study was carried out with a sample of 42 adolescents in 5th and 6th grades of high school, selected through the application of the Beck Depression Inventory II; subs equently, the modified Coping Strategies Scale (EEC them. The results indicated that these adolescents use more emotion-- M) was applied to focused strategies than problemfocused ones. Of the emotion used by mafocused ones, emotional avoidance was the most les older than 17 years, and the least used by males aged 17 years was religion. Autonomy was the problemfocused strategy most used by males, while females were more likely to use aggressive reaction. Adolescents with mild depressive symptomatology used m ore problem solving, denial and cognitive avoidance; those with mild and moderate symptomatology levels used more autonomy and emotional avoidance, and those with severe symptomatology used more aggressive re Key words: copin action and emotional avoidance.